A comprehensive review of summer savory (Satureja hortensis L.): promising ingredient for production of functional foods - Ejaz, Afaf; Waliat, Sadaf; Arshad, Muhammad Sajid; Khalid, Waseem; Khalid, Muhammad Zubair; Rasul Suleria, Hafiz Ansar; Luca, Marian-Ilie; Mironeasa, Costel; Batariuc, Ana; Ungureanu-Iuga, Mădălina; Coţovanu, Ionica; Mironeasa, Silvia (Frontiers in Pharmacology, 2023)
This review aims to measure the different aspects of summer savory including biological activity, medicinal properties, nutritional value, food application, prospective health benefits, and its use as an additive in broiler feed. Furthermore, toxicity related to this is also overviewed. Summer savory leaves are abundant in total phenolic compounds (rosmarinic acid and flavonoids) that have a powerful antioxidant impact. Rosmarinic (α-O-caffeoyl-3,4-dihydroxy-phenyl lactic) acid has been identified in summer savory as a main component. According to phytochemical investigations, tannins, volatile oils, sterols, acids, gums, pyrocatechol, phenolic compounds, mucilage, and pyrocatechol are the primary compounds of Satureja species. Summer savory extract shows considerable biological potential in antioxidant, cytotoxic, and antibacterial assays. Regarding antioxidant activity, summer savory extract displays an inhibitory effect on lipid peroxidation. Summer savory also has Fe (III) reductive and free radical scavenging properties and contains minerals and vitamins. Summer savory has important biological properties, including antimicrobial activity and antioxidant activity, and protective effects against Jurkat T Cells, Alzheimer’s disease, cancer, infection, cardiovascular diseases, diabetes, and cholesterol. The leaves and stems of this plant are employed in the food, feed, and pharmacological industries due to their antioxidant properties and substantial nutritional content. Conclusively, summer savory is widely considered beneficial for human health due to its versatile properties and medicinal use.